Swaposin domain of potato aspartic protease (StAsp-PSI) exerts antimicrobial activity on plant and human pathogens - Muñoz, Fernando F. (2010)
Plant-specific insert domain (PSI) is a region of approximately 100 amino acid residues present in most plant aspartic protease (AP) precursors. PSI is not a true saposin domain; it is the exchange of the N- and C-terminal portions of the saposin like domain. Hence, PSI is called a swaposin domain. Here, we report the cloned, heterologous expression and purification of PSI from StAsp 1 (Solanum tuberosum aspartic protease 1), called StAsp-PSI. Results obtained here show that StAsp-PSI is able to kill spores of two potato pathogens in a dose-dependent manner without any deleterious effect on plant cells. As reported for StAPs (S. tuberosum aspartic proteases), the StAsp-PSI ability to kill microbial pathogens is dependent on the direct interaction of the protein with the microbial cell wall/or membrane, leading to increased permeability and lysis. Additionally, we demonstrated that, like proteins of the SAPLIP family, StAsp-PSI and StAPs are cytotoxic to Gram-negative and Gram-positive bacteria in a dose dependent manner. The amino acid residues conserved in SP_B (pulmonary surfactant protein B) and StAsp-PSI could explain the cytotoxic activity exerted by StAsp-PSI and StAPs against Gram-positive bacteria. These results and data previously reported suggest that the presence of the PSI domain in mature StAPs could be related to their antimicrobial activity